SANKSI PIDANA (ISLAM) DALAM PERSPEKTIF FILSAFAT DAKWAH - Gazali, Ahmad (UIN Antasari Banjarmasin, 2017)
Penal sanctions in Islam on more. Because the basic principle of criminal practice in Islamic justice is